PENGARUH HARGA SAHAM TERHADAP NILAI PERUSAHAAN DENGAN ISLAMIC SOCIAL REPORTING SEBAGAI PEMODERASI Studi pada Perusahaan Telekomunikasi yang terdaftar di Jakarta Islamic Index) - alfina, alfialfina; Muhammad Salman; Tuti Meutia (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This study aims to determine the Effect of Stock Prices on Company Value with Islamic Social Reporting (ISR as a Moderator in Telecommunication Companies Listed on the Jakarta Islamic Index (JII). The objects of this study are companies listed on the Jakarta Islamic Index (JII). The sampling technique uses the purposive sampling method. The data collection method used in this study is the documentation method and literature study. The data analysis method used in this study is moderated regression analysis (MRA), by operating SPSS Software. The results of this study indicate that the stock price variable has a negative and significant effect on company value, the stock price variable with Islamic social reporting as a moderator has a positive and significant effect on company value, so that Islamic Social Reporting can moderate company value in telecommunications companies listed on the Jakarta Islamic Index (JII). The limitations of the study are that the variables used only include Stock Price, Company Value, and Islamic Social Reporting. The results will be different if further researchers add other variables related to the study. The sample used was only 3 (three) companies in a 10-year period, namely 2013-2022. The objects studied were only telecommunications companies listed on the Jakarta Islamic Index (JII).